Solusi Ramah Lingkungan Mengolah Sampah Organik Melalui Budidaya Maggot Di Pesantren Ulumul Quran Stabat Kabupaten Langkat - Arief Marizki Purba; Agus Suriadi; Muhammad Husni Thamrin; Faiz Albar Nasution (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
The drastic increase in the volume of organic waste is an unavoidable consequence of population growth and rapid development, both in rural and urban areas. This condition is exacerbated by urbanization and rising living standards, which are directly correlated with an increase in per capita waste production. The phenomenon of urbanization, particularly in Indonesia, has led to a concentration of population in urban areas, which in turn has resulted in a rapid increase in waste generation. Existing management capacity is often inadequate to handle this ever-increasing volume of waste, leading to serious accumulation and environmental pollution. Islamic boarding schools, as Islamic educational institutions, have great potential for managing the environment based on a circular economy. This institution, with its values of independence and togetherness, has strong social capital to initiate and implement sustainable waste management practices integrated with circular economy principles, as demonstrated in several community-based programs. Various initiatives have proven that pesantren are capable of developing independent business units thru waste utilization, for example, in the innovation of organic fertilizer from livestock manure. This community service program was conducted at the Ulumul Qur'an Islamic Boarding School in Stabat, Langkat Regency, with the aim of optimizing organic waste management thru the cultivation of Black Soldier Fly (BSF) or maggots as an environmentally friendly solution and an entrepreneurial opportunity for students. The methods used included socialization, technical training, and the Participatory Learning and Action (PLA) approach to encourage active student involvement. The results of the activity showed an increase in students' understanding of organic waste management, the utilization of boarding school land for maggot cultivation, and the development of environmentally based entrepreneurial skills. This program not only reduces the volume of organic waste but also produces economically valuable alternative feed that can support agriculture and livestock farming. Thus, this activity contributes to the creation of a sustainable waste management system in pesantren while also supporting the economic empowerment of students.